New Surviving Sepsis Campaign guidelines: back to the art of medicine. Issue 1 (12th July 2018) - Scala, Raffaele; Schultz, Marcus; Bos, Lieuwe D.J.; Artigas, Antonio
Despite the gain in terms of hospital survival achieved in the last decades though the application of Surviving Sepsis Campaign (SSC) guidelines, the treatment of sepsis remains challenging for clinicians as more than one in four septic patients is still likely to die in hospital. In this editorial, we would like to remark on the most important novelty introduced by the new SSC guidelines [1] that we believe represent an advanced step in the implementation of precision medicine in this field of respiratory and intensive care medicine. Although is sensible that the SSC evidence-based recommendations remain a "must" in the bundled usual care of the majority of septic patients, it should be borne in mind that the comprehensive panel of the advice provided by these guidelines might not fit all cases in all clinical scenarios [1]. Accordingly, an individualised approach based on best-practice statements is likely to be coherently considered in these specific circumstances. We therefore want to highlight the existing obstacles that limit the capability of these new guidelines of having a strong impact on clinical outcomes of sepsis around the world [2]. Surviving Sepsis Campaign guidelines represent an advanced step in the implementation of precision medicine in this field of respiratory and intensive care medicine, where evidence-based recommendations are integrated with best-practice suggestions http://ow.ly/hlk230ko1GN